The crux how leaders become strategists - Rumelt, Richard (New York Public Affairs, 2022)
Rumelt defines the essence of the strategists skill with vivid storytelling, from how Elon Musk found the crux that propelled the success of SpaceX to how the American military came to grips with the weaknesses of its battle strategy. Musk?s core challenge, for example, was rocket reusability. His intense focus on the soft landing of SpaceX?s rockets enabled them to be used again?radically reducing the cost of putting a pound in orbit. Musk?s strategy was not based on how value is created or how to position SpaceX in its industry. It was a design for action, the mental maneuver that focuses energy on what really made a difference through understanding the crux and creating an effective response that led to breakthrough
Includes bibliographical references and index.
Keywords: Strategic planning. | Management. | Leadership